Proteomics and metabolic profiling of Vibrio parahaemolyticus at three different temperatures - Meng, Aiyun; Tu, Zhigang; Hu, Linlin; Chen, Fuxiao (Frontiers in Marine Science, 2025)
IntroductionMicroorganisms exist and survive in complex and variable environments. Bacteria communities response and adapt to the changing conditions. The Mechanisms underlying bacterial survival can be elucidated through the use of multi-omics techniques.MethodsIn this study, we test an approach for measuring how different temperatures (4°C, 25°C, and 37°C) affected bacterial physiological functions. Proteomic and metabolomic analyses were conducted on Vibrio parahaemolyticus LF1113 under different temperatures.Results and discussionA total of 2,899 proteins and 396 metabolites were identified. The differentially expressed proteins (DEPs) and differentially metabolites (DMs) were involved in Lysine degradation, metabolic pathways, ABC transporters, and microbial metabolism in diverse environments pathways. An integrated metabolomics/proteomics analysis approach was employed in this study. The analysis of both types of data information (proteins and metabolites) aids to reveal the microbial adaptive regulation in response to temperature stimuli. The study can further help clinical research of V. parahaemolyticus from the perspective of metabolomics and proteomics.